THE RIGHT ON LAND FOR FOREIGNER AND FOREIGN LEGAL ENTITY TOURISM INVESTASION PERSPECTIVE, PARTICIPATION AND NOMINEE PRACTICE PREVENTION - Siti Hafsyah Idris; Djelantik, IGN. Supartha; Budiartha, I Nyoman Putu (Journal Equity of Law and Governance, 2021)
Bali is one of the national cultural heritages, which is endlessly praised in various essays and research results, then becomes a reference and promotion as an exotic island that inspires the rise of world tourism. Tourism encourages investment in hospitality, restaurants, transportation, trade, property, the creative economy sector and others. Investment, changing the function of agriculture into hospitality and transforming the work of farmers into services. Major changes in the mind-set of rural farmers to urban services. The purpose of this study is to find out the concept of norms and substance of the basic Agrarian Law and the laws and regulations in land ownership/ Provision of Residential for foreigners/Foreign Legal Entity. This research applies a socio-legal approach. This change is not accompanied by a significant expansion of public participation, because tourism is concentrated in capital due to legal limitations that favoring on investors..The results of the study are expected to encourage the weight of the substance of the Foreigners Residential Provision legislation, containing the substance of the Foreigners Residential Provision regulatory norms carrying the message of community participation as social engeeneer and community expectations (das sollen), global.